2019
DOI: 10.1111/ijac.13431
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of YSZ porous ceramics with precise porosity control

Abstract: Conventional preparation of porous ceramics often hard to accurately control the porosity of the samples. In this paper, by improving the foaming method, the foaming process is placed in the limited space of the ball mill tank, and YSZ porous ceramics with different porosity are obtained by changing the amount of slurry. Initial results showed that the porosity of the sample varies linearly with the increasing of addition of slurry. From the microscopic morphology, it can be seen that the increase in slurry co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The micromechanical modeling of porous polycrystalline ceramics under different loadings shows two fracture initiation mechanisms due to stress concentration at the pore boundary. 22 Deformation was analyzed under tension and compression. The scientists found that polycrystalline ceramic material splits mostly intergranular due to the grain boundary’s lower fracture toughness than the grains.…”
Section: Introductionmentioning
confidence: 99%
“…The micromechanical modeling of porous polycrystalline ceramics under different loadings shows two fracture initiation mechanisms due to stress concentration at the pore boundary. 22 Deformation was analyzed under tension and compression. The scientists found that polycrystalline ceramic material splits mostly intergranular due to the grain boundary’s lower fracture toughness than the grains.…”
Section: Introductionmentioning
confidence: 99%
“…Limited volume foaming process is a preparation technology of porous ceramics which can accurately control the porosity of samples [1]. The foaming is limited in the ball milling tank, and the space in the ball milling tank is…”
Section: Introductionmentioning
confidence: 99%
“…
Porous YSZ ceramics with different pore structure were prepared by volume limiting foaming technology. Accurate porosity could achieve by this technology [1], so all samples were adjusted to density of 1g/m 3 (porosity of about 82.6%). For the same density, the in uence of porosity change on the strength was excluded.
…”
mentioning
confidence: 99%
“…Lang et al [17] dealt with construction of YSZ porous ceramics with precise porosity control. Current preparation of porous ceramics usually hard to exactly control the porosity of the samples.…”
Section: Introductionmentioning
confidence: 99%